The limits of Quediini at last (Staphylinidae: Staphylininae): a rove beetle mega‐radiation resolved by comprehensive sampling and anchored phylogenomics. (17th March 2021) - Brunke, Adam J.; Hansen, Aslak K.; Salnitska, Maria; Kypke, Janina L.; Predeus, Alexander V.; Escalona, Hermes; Chapados, Julie T.; Eyres, Jackson; Richter, Robin; Smetana, Aleš; Ślipiński, Adam; Zwick, Andreas; et al.
Abstract: Rove beetles of the tribe Quediini are abundant predators in humid microhabitats of forested, open, synanthropic or subterranean ecosystems, with just over 800 species distributed across the temperate and subtropical regions of the Northern Hemisphere. Previous molecular phylogenies included only a limited representation of this diversity but have already indicated that Quedius, containing the majority of Quediini species, is polyphyletic. Six genera, historically associated with Quediini but now Staphylininae incertae sedis, are known only from few pinned specimens and have never been sequenced. Recent synergy between target enrichment phylogenomics, low‐input sequencing of dry, pinned insect specimens and advances in alpha taxonomic knowledge have made comprehensive sampling of Quediini tractable. Here we developed a novel probe set specialized for anchored hybrid enrichment of 1229 single‐copy orthologous loci in Staphylinidae. In one of the largest target enrichment phylogenies of insects to‐date, we sequenced 201 ingroup taxa to clearly delimit monophyletic Quediini within Staphylininae and resolve relationships within this tribe, with 46% of sampled taxa derived from pinned specimens (0–45 years old). Maximum likelihood and coalescent phylogenetic analyses produced well‐resolved, congruent topologies that will serve as a framework for further exploration of this radiation and its necessary generic revision. The inclusion of nearly all remaining Staphylininae incertae sedis genera, all known only from pinned specimens, resulted in the creation of Quelaestrygonini Brunke, trib. n. and revised concepts for Cyrtoquediini and Indoquediini. Quediini was resolved as monophyletic with the transfer of Q. elevatus and Q. nigropolitus to other tribes but Quedius and its subgenera Microsaurus, Distichalius and Raphirus were shown to be para‐ or polyphyletic. Based on the results of our analyses, Velleiopsis Fairmaire, 1882 syn. n. and Megaquedius Casey, 1915 syn. n. are synonymized with Microsaurus Dejean, 1833 resulting in: Q. ( Microsaurus ) marginiventris (Fairmaire) comb. n., Q. ( M. ) varendorffi (Reitter) comb.n. Several species of Quedius were transferred from Microsaurus to Distichalius ( Q. aethiops Smetana, Q. biann Smetana, Q. cingulatus Smetana and Q. taruni Smetana), Distichalius to Raphirus ( Q. fagelianus Scheerpeltz) and Microsaurus to Raphirus ( Q. mixtus Eppelsheim and Q. persicus Korge). Abstract : Novel probe set developed for anchored hybrid enrichment of Staphylinidae (Coleoptera), targeting 1229 single‐copy, protein‐encoding, orthologous loci from the nuclear genome. Comprehensive phylogeny of rove beetle tribe Quediini (∼800 spp.), with 46% of 201 ingroup taxa sequenced from pinned specimens, will serve as framework for needed generic revision. We resolved seven major clades within monophyletic Quediini and systematically place nearly all remaining Staphylininae incertae sedis genera, resulting in Quelaestrygonini trib. n., and revised concepts for Cyrtoquediini and Indoquediini.